2020
DOI: 10.1007/s42729-020-00181-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration in Irrigated and Rain-Fed Cropping Systems Under Long-Term Fertilization Regimes

Abstract: It is important to understand soil organic carbon (SOC) sequestration and its relationship with crop productivity. Based on two long-term experiments under irrigated vs rain-fed conditions conducted in the China Loess Plateau, we evaluated SOC sequestration efficiency under diverse fertilization regimes and quantified the relationship between crop yield and SOC. The experiments consisted of a winter wheat-summer maize system under irrigated conditions with nine treatments-nitrogen (N), N and phosphorus (P), N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Moreover, SOC values were higher during the wheat compared to maize season in the entire profile. This is thought to be because increased rainfall during the maize season have resulted in a relatively higher soil moisture content, resulting in a more favorable soil environment for rapid propagation of soil microorganisms, and subsequent acceleration of SOC mineralization and decomposition ( Silver & Miya, 2001 ; Wang et al, 2020 ; Zhang et al, 2010 ). In contrast, during the winter wheat growth period, rainfall was lower, and activity of microorganisms in the soil was likely to be lower, thereby slowing the rate of SOC decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SOC values were higher during the wheat compared to maize season in the entire profile. This is thought to be because increased rainfall during the maize season have resulted in a relatively higher soil moisture content, resulting in a more favorable soil environment for rapid propagation of soil microorganisms, and subsequent acceleration of SOC mineralization and decomposition ( Silver & Miya, 2001 ; Wang et al, 2020 ; Zhang et al, 2010 ). In contrast, during the winter wheat growth period, rainfall was lower, and activity of microorganisms in the soil was likely to be lower, thereby slowing the rate of SOC decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, conservation and storage of SOC in arable soil is becoming increasingly important because of the beneficial effects on soil fertility and subsequent improvements in crop yield, not to mention the mitigating effects on climate change ( Baveye et al, 2018 ; UNEP, 2017 ). In much of China, wheat and maize yield responses reach a plateau at SOC levels of 21.8–46.2 and 22–44.4 Mg ha −1 , respectively ( Wang et al, 2020 ). Soil and crop management practices have a significant effect on C and N cycles in cultivated land, altering the quantity and quality of crop residues in the soil as well as the overall supply of nutrients ( Dou et al, 2018 ; McDaniel et al, 2014 ; Tian et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that long-term balanced fertilization, especially with organic supplements, significantly increased SOC and TN contents over control, but soil pH showed the opposite trend. This can be attributed to the greater effects of balanced fertilization on the growth of crops, thereby bringing about a larger amount of organic matter from crop residues, i.e., roots, root exudates, stubbles, and other debris into soils; and direct organic carbon input through crop straw/stalk return or manure for treatments with organic supplements, such as SNPK and MNPK [55]. Reduction in pH can be due to the addition of synthetic fertilizers, especially nitrogen fertilizer [56], and the organic acid generated from mineralization of organic matter investment through the ways stated above.…”
Section: Responses Of Soil Chemical Properties To Fertilization Regimesmentioning
confidence: 99%
“…Gongzhuling, China Maize 6 2.07 [103] Organic fertilizer (2.8 Mg• ha −1 • yr −1 C & 47.2 kg• ha −1 • yr −1 N) vs no fertilizer Gujarat, India Groundnut 16 100 0.63 [104] Organic (1.98 Mg• ha −1 • yr −1 C & 15.6 kg• ha −1 • yr −1 N) plus inorganic fertilizers (15.6 kg• ha −1 • yr −1 N) vs no fertilizer Gujarat, India Groundnut 16 100 0.43 [104] Inorganic fertilizer (20:40:40 kg• ha −1 • yr −1 N: P2O5:K2O) vs no fertilizer Gujarat, India Groundnut 16 100 0.1 [104] Cattle slurry (240 kg• ha −1 • yr −1 N) vs no input, P, K & S applied Kiel, Germany Continuous silage maize 8 30 0.1 [105] Cattle slurry (160 kg• ha −1 • yr −1 N) vs no input, P, K & S applied Kiel, Germany Oats-wheat-pulses rotation 8 30 0.3 [105] Cattle slurry (160 kg• ha −1 • yr −1 N) vs no input, P, K & S applied Kiel, Germany Maize/oats-wheatley rotation 8 30 0.4 [105] Organic fertilizer (15 Mg• ha −1 • yr −1 ) vs no fertilizer, P, K, rotation with 100% cereal, SR from barley and rye Berlin, Germany Barley-barley-ryeoats 24 20 0.1 [106] Organic fertilizer (15 Mg• ha −1 • yr −1 ) vs no fertilizer, P, K, rotation with 75% cereal, SR from barley and rye Berlin, Germany Beets-barley-rye-rye 24 20 nc [106] Organic fertilizer (15 Mg• ha −1 • yr −1 ) vs no fertilizer, P, K, rotation with 50% cereal, RR from barley and rye Berlin, Germany Beets-barley-ryesilage maize 24 20 0.03 [106] Straw incorporated (2.25 Mg• ha −1 • yr −1 ) vs no straw, ST, 240 kg• ha -1 • yr -1 urea-N & P Quzhou, China Wheat-maize 34 20 1.76 [97] Straw incorporated (4.5 Mg• ha −1 • yr −1 ) vs no straw, ST, 240 kg• ha -1 • yr -1 urea-N & P Quzhou, China Wheat-maize 34 20 2.44 [97] Straw mulch vs no organic matter input, fertilizer rates and forms varied Lopburi, Thailand Maize-mung bean 5 15 0.39 [101] SR vs straw removal, irrigation and inorganic fertilisers (352.5:82.2:146.3 kg• ha −1 • yr −1 N:P:K) Shaanxi, China Wheat-maize 25 20 0.11 [107] Irrigation vs rainfed, no fertilizer Shaanxi, China Wheat-maize 25 20 0.03 [107] Rotation vs continuous Global review 25 (Average) 22 (Average) 0.15 [16] With vs without catch crop Argentina Soybean 8 20 0.09−0.39 [108] Note: NT, no-tillage; ST, standard tillage; RT, rotary tillage; SR, straw return. nc, no substantive change.…”
Section: Madrid Spainmentioning
confidence: 99%